Streamlining of planning approval workflow process for town and country planning department of ACCRA, Ghana - Kweku, Hammah Noriss (2013)
In a complex planning (service) organization such as the Town and Country Planning Department (TCPD) in Ghana, proposing a restructured model to streamline the planning approval process and curtail delays entails consideration and questioning of many established techniques and protocols—this is a challenge because of the sensitivity surrounding the intended actions. The proposition that ‘knowledge’ should be considered as a contingency factor whereas ‘discontinuous’ and ‘reach’ should be considered as organizational design parameters (individual, group, organization and inter-organization) was an early effort by Ibrahim & Nissen (2007) to fit the complex environment within the Contingency Factors outlined by Burton & Obel (2004). However, while Burton & Obel's Contingency Factors support organizational performance optimization, this study agrees with Ibrahim (2005) who found them deficient in their ability to improve or optimize service organizations such as those involved in property development or urban planning agencies. Therefore, this study was drawn towards a phenomenon concept by Ibrahim & Paulson (2008) who also described an operating environment called discontinuity in organization (DIO) where a member of a project team would enter when needed or leave when a task is completed during the progression of a project. The DIO phenomenon is detrimental to organizations such as planning agencies as succinctly put by Ibrahim & Nissen (2007) that “knowledge flow enables workflow and workflow drives performances”. Building on the operational concept by Ibrahim & Nissen (2007) which posited that “the explicitness level of knowledge is key to determining how effective and efficient an organization would be in various properties and structural configuration fit”, the TCPD and planning agencies must anticipate in ‘what different and various streamlined’ strategies an attempt can be made to find better solutions. Such solutions can curtail identified delay directness issues and thus broadens the chances of better solutions. Using housing deficits as a motivational question, the study explores and answers the organizational root cause of the delays in the building permit issuance by TCPD. Exploring this in only one way is not recommended because the study finds such a limited approach may skew the potential solutions offered. Therefore the study used two methods of approach to arrive at strong empirical findings. The first approach utilised a Case Study qualitative analysis method while the second adopted system analysis method using the Virtual Design Team’s (VDT) (Jin & Levitt, 1996) computational organizational simulations. The data was collected through multiple sources of evidence to investigate into the workflow process of a planning approval delayed case. Using a COT software called SimVision™ for COT modelling, the study restructured three sequential workflows of the current approval procedure of TCPD into a single workflow. The current project duration was considerably reduced from a total of 161 days to 39 days in the final Alternative Restructured Model. A presentation of the proposed Alternative Restructured Model to a group of 16 professionals and key members of the TCPD and STCM planning approval system in Ghana was also conducted to gain validation accounts. Results from the validation processes affirmed that the restructuring recommendations are possible. However, feedback highlighted which recommendations would be easy to implement whilst also highlighting others which would require legislative approval. The results provided empirical support to show that in a dynamic organization such as the TCPD — ‘organizational streamlining’ success depends on the relative emphasis of discontinuous membership as structure configuration as per parameter property reach (individual, group, organization and interorganization). Consequently, this study contributes in providing empirical support for Ibrahim & Nissen (2007) where they had earlier recommended further studies to determine if knowledge can be the seventh Contingency Factor to Burton & Obel’s (2003) organizational design—with discontinuous as a new structural configuration. Additionally, it contributes towards closing the problematic fracture between organizational theory versus the practicalities and capabilities of service organizations by addressing the issues of organizational structural rigidity. The study also proposes alternatives in terms of operational fitness that could evaluate specific strategies for ‘streamlining’ and ‘applicability’ in the essence of various theories applied. The study finally concludes with a summary of how it contributes in two major disciplines: organizational and management.